Dahlia mixtecana (Asteraceae, Coreopsideae), a striking new species from Oaxaca, Mexico - Reyes-Santiago, Jerónimo; Islas-Luna, María De Los Ángeles; Munguía-Lino, Guadalupe; Castro-Castro, Arturo (Phytotaxa, 2019)
Dahlia mixtecana (Asteraceae, Coreopsideae) is described and illustrated as a new species endemic to western Oaxaca, Mexico. This taxon is related to Dahlia sect. Dahlia and Dahlia sect. Entemophyllon. However, based on the current evidence available and the current system of infrageneric groups, it does not appear possible to assign the new species with confidence to any taxonomic section. The description of the new species is presented with distribution maps, illustrations, photographs, discussions on the taxonomic relationship and an identification key to the sections and species of Dahlia occurring in Oaxaca and species in Dahlia sect. Entemophyllon related to D. mixtecana.